Self-powered wearable breath sensor cum nanogenerator using AuNR-rGO-PVDF nanocomposite - Bang, Amruta D.; Ghalawat, Monika; Poddar, Pankaj; Kulkarni, Sulabha K.; Adhyapak, Parag V. (IEEE Sensors Journal, 2023)
Breathing is the most important function of living being. It is well known that breath contains 90% humidity along with various gases and volatile organic compounds (VOCs). These gases are released during various metabolic activities in the body. These gases present in the breath can act as biomarkers to showcase healthiness or abnormalities in the body. Therefore, breath sensors are the need of time to detect diseases at early stages and in noninvasive way. Herein, we report, simple breath sensor using Au nanorods (AuNRs) and its nanocomposite with reduced graphene oxide (rGO) and polyvinylidene fluoride (PVDF). The nanocomposites system is designed in such a way that each component has its advantages for breath sensing. Here, AuNR being a good humidity sensitive material detects the breath efficiently. The ss phased PVDF being a very good ferroelectric material, contributes for voltage generation during sensing and enables the device to be self powered. The highly conducting rGO increases the sensitivity and voltage generation by facilitating the electron transport in the nanocomposite system. The nanocomposite was optimized with respect to PVDF, rGO and Au concentration. The as-synthesized materials were characterized by physiochemical characterization techniques such as field emission scanning electron microscopy (FESEM), X-ray diffraction analysis (XRD), UV-Visible spectroscopy, Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS). The ss phase formation of the PVDF was confirmed from the XRD peak at 20.41 degrees. SEM results revealed that AuNR have length 15-20 nm and aspect ratio similar to 3-4. Breath sensing tests were carried out for as synthesized nanocomposite material. The nanocomposite exhibited high sensitivity towards breath and generated the voltage of similar to 0.7 V within 0.8 s.
Keywords: Au nanorods (AuNRs); breath analyzer; breath sensor; nanogenerator